Bio-milling technique for the size reduction of chemically synthesized BiMnO3 nanoplates - Mazumder, Baishakhi; Uddin, Imran; Khan, Shadab; Ravi, Venkat; Selvraj, Kaliaperumal; Poddar, Pankaj; Ahmad, Absar (Journal of Materials Chemistry, 2007)
Wet- chemical techniques for the synthesis of complex oxide materials have advanced significantly; however, achieving finely dispersed nanoparticles with sizes less than 10 nm still remains challenging, especially for the perovskite family of compounds. On the other hand, a fungusmediated synthesis technique has recently shown potential to synthesize perovskites such as BaTiO3 with sizes as small as 5 nm. Here we report, for the first time, the use of fungal biomass, at room temperature, to break down chemically synthesized BiMnO3 nanoplates ( size similar to 150 - 200 nm) into very small particles (, 10 nm) while maintaining their crystalline structure and the phase purity. This novel technique that we have named as `` bio- milling'' holds immense potential for synergically utilizing both chemical and biological synthesis techniques to synthesize complex oxide nanoparticles with particle sizes less than 10 nm with the proper crystalline phase.

Fungus-based synthesis of chemically difficult-to-synthesize multifunctional nanoparticles of CuAlO2 - Ahmad, Absar; Jagadale, Tushar C.; Dhas, Vivek V.; Khan, Shadab; Patil, Shankar; Pasricha, Renu; Ravi, Venkat; Ogale, Satishchandra B. (Advanced Materials, 2007)
Fungal nanosynthesis of ternary CuAlO2 phase is achieved at 50 degrees C. This phase is chemically difficult to synthesize at low temperatures because of the incompatible oxidation chemistry of Cu and Al. The synthesized protein-capped water-dispersible nanoparticles show blue luminescence and radio-frequency absorption (see figure).

Novel synthesis of SrBi2Nb2O9 powders from hydroxide precursors - Gupta, Upendra Nath; Rao, Koteswara; Pradhan, Sivaram; Jha, Ratnesh Kumar; Muthurajan, Harries; Ravi, Venkat (International Journal of Applied Ceramic Technology, 2008)
Simple hydroxide precursors were used for the first time for the synthesis of a typical Aurivillius compound (SrBi2Nb2O9 (SBN)) at a low temperature. This method is very advantageous because it circumvents the use of SrCO3 in the case of conventional ceramics as well in the coprecipitation methods, thereby lowering the formation of the product phase. Commercially purchased strontium hydroxide is mixed thoroughly with freshly precipitated bismuth and niobium hydroxides in a stoichiometric ratio and heated at different temperatures ranging from 100 degrees C to 750 degrees C for 12 h. The sequence of the reaction and evolution of the product phase was monitored by X-ray diffraction (XRD) studies by recording the XRD for samples calcined at different temperatures. The incipient SBN phase begins to form at temperatures as low as 400 degrees C, and phase formation was complete only at 650 degrees C as revealed by the XRD observations. The differential thermal/thermogravimetric analyses) also corroborate this result. The morphology and average particle size of these powders were investigated by transmission electron microscopy studies.